PROPERTIES OF THE SURFACE WAVE IN THE PLANAR GROUNDED DIELECTRIC STRUCTURE EXCITED BY A TWO-LAYER MICROSTRIP GRATING - Seleznyov, D. G.; Reznik, I. I. (Видавничий дім «Академперіодика», 2018)
PACS numbers: 41.20.Jb,84.40.BaPurpose: Determining the amplitude and phase characteristics of the surface wave in a planar dielectric structure excited by a two-layer microstrip array of rectangular radiators and ascertaining the possibilities of using it to excite the phased antenna arrays from segments of rectangular waveguides.Design/methodology/approach: The research method is based on application of the spectral method in approximation of a given distribution of surface current density on the array radiators, which is given by a function which describes the true current distribution fairly well and is convenient for further analysis. The essence of the spectral method is in representation of the Green’s function, the radiation field, and the current density as expansions in the Fourier integral. The investigations were carried out with taking into account the presence of surface waves in the dielectric layers and the mutual influence of the radiators.Findings: Using the developed technique, an algorithm for calculating the characteristics of a surface wave excited by a twolayer microstrip array of rectangular radiators is constructed. Analysis of the amplitude-phase distribution of electromagnetic field showed that at distance of  ≥1.5λ of the grating edge the magnitude of the amplitude of the field of surface wave becomes practically constant, and its value in the case of a twolayer grating is approximately twice as large as in the case of a single-layer grating. It is established that in this structure it is possible to obtain an almost linear phase distribution of the electromagnetic field in the surface wave, and by shifting the phases of the current on the microstrip radiators to change its slope.Conclusions: The amplitude-phase characteristics of a surface wave in a planar dielectric structure excited by a two-layer microstrip array of rectangular radiators are investigated and the perspective of its application as a source of excitation of a phased antenna array from segments of rectangular waveguides are shown.Key words: surface wave, two-layer microstrip grating, spectral method, phased antenna arrayManuscript submitted 03.08.2018Radio phys. radio astron. 2018, 23(4): 294–301REFERENCES1. GRIBOVSKY, A. V., 2001. Properties of Phased Antenna Array of Rectangular Wavegardes Excited by Surface Wave. Radio Phys. Radio Astron. vol. 6, is. 4, pp. 332–336. (in Russian).2. GRIBOVSKY, A. V., KUZMICHEV , I. K. and SELEZNEV, D. G., 2008. Phased Antenna Array. Ukraine Patent No. 83038.3. KUSAYKIN, O. P., MELEZHIK, P. N., POYEDINCHUK, A. E., PROVALOV, S. A. and SELEZNYOV, D. G., 2016. Surface and leaky waves of a planar dielectric waveguide with a diffraction grating. IET Microw. Antennas Propag. vol. 10, is. 1, pp. 61–67. DOI: https://doi.org/10.1049/iet-map.2015.01584. PROSVIRNIN, S. L. and NECHAEV, YU. B., 1992. Designing of microstrip antennas by using approximation of fixed surface current distribution. Voronezh, Russia: Voronezh State University Publ. (in Russian).5. PROSVIRNIN, S. L., REZNIK, I. I. and SELEZNEV, D. G., 1998. Matching with feed lines and taking into account interaction in microstrip antenna arrays. J. Commun. Technol. Electron. vol. 43, no. 12, pp. 1376–1379.6. SELEZNYOV, D. G., REZNIK, I. I. and SELEZNYOV, A. D., 2003. Microstrip Antenna Arrays Composed of Rectangular Radiators. Radio Phys. Radio Astron. vol. 8, is. 1, pp. 52–58. (in Russian).7. SELEZNYOV, D. G., REZNIK, I. I. and SELEZNYOV, A. D., 2005. Microstrip Antenna Arrays with Dielectric Covering. Radio Phys. Radio Astron. vol. 10, is. 1, pp. 85–91. (in Russian).8. SELEZNEV, D. G., REZNIK, I. I. and SELEZNEV, A. D., 2005. Structure Synthesis of Linear Microstrip Phased Antenna Arrays. Radio Phys. Radio Astron. vol. 10, is. 2, pp. 150–156. (in Russian).9. GRIBOVSKY, A. V., REZNIK, I. I. and SELEZNYOV, D. G., 2011. Properties of surface wave in the planar grounded dielectric structure excited by a microstrip grating. Phys. Wave Process. Radio System. vol. 14, is. 2, pp. 32–38. (in Russian).10. SELEZNYOV, D. G. and REZNIK, I. I., 2018. Two-Layer Microstrip Antenna Arrays of Rectangular Radiators. Radio Phys. Radio Astron. vol. 23, is. 3, pp. 203–211. (in Russian). DOI: https://doi.org/10.15407/rpra23.03.20